Marketing Strategy Using Swot Analysis in Increasing Sales of Amanah Products: A Case Study On PT. UPS Pawnshop Simpang Lima Banyuwangi - Nur Hafidoturrohmah; Lely Ana Ferawati Ekaningsih; Imam Muslih (Electronic Journal of Education, Social Economics and Technology, 2025)
This study aims to analyze the marketing strategy of Amanah products of PT. UPS Simpang Lima Banyuwangi Pawnshop uses SWOT analysis. As one of the company's main products, Amanah offers vehicle financing for micro-entrepreneurs, employees, and professionals with low administration fees and fixed installments. Despite these advantages, Amanah market performance faces challenges from the lack of public awareness and competition from other financial institutions that offer similar products. Through qualitative descriptive research, this study identifies the main strengths, weaknesses, opportunities, and threats of Amanah Products. The results of the study show that Amanah benefits from the reputation of PT. Pegadaian, an extensive branch network, and flexibility in financing, while also highlighting areas of improvement such as digital promotions and more competitive down payment requirements. This SWOT analysis provides strategies to strengthen product awareness, adjust to customer needs, and expand the customer base.